Penanaman Bibit Cabai Rt 21 Rw 05 Kelurahan Betungan Kecamatan Selebar Kota Bengkulu - Yulista, Yulista; Alliyo, Aswin; Saputra, Aldi Pernandes; Amri, Bahrul; Cahyadi, Elham; Lismana, Oetari; Asnawati, Asnawati; Perdima, Feby Elra (Jurnal Kewirausahaan & Inovasi, 2025)
The 2025 Dehasen Bengkulu University Community Service Program (KKN) was held in RT 21 RW 05, Betungan Village, Selebar District, Bengkulu City. The work program implemented during the KKN period is "Planting Chili Seeds". This work program aims to make the community aware of how to plant chili seeds effectively and efficiently. So that the outputs that are desired from this activity are scientific articles in the Community Service Journal, activity videos published on GoogleDrive and the Final Report in the form of the UNIVED Bengkulu Thematic KKN Implementation Results Report. The methods used in the Thematic Community Service Program (KKN) are the participation method, observation, interview, library study and documentation.